Determination of Adaptation Capabilities of some Durum Wheat Genotypes of Foreign Origin in Southeast Anatolian Region - Sertaç TEKDAL; Enver KENDAL; Hüsnü AKTAŞ; Mehmet KARAMAN; Hasan DOĞAN; Hasan KILIÇ; Halil KARAHAN (Trakya University Journal of Natural Sciences, 2015)
This study was performed in growing season of 2011-2012 in Diyarbakır and Kızıltepe, representing two important subregions of Southeast Anatolia Region, in order to identify durum wheat genotypes having superior adaptaptation capabilities and quality features to be used in breeding programs. The material used in the study included 18 lines and 5 control varieties (Omrabi5, Younes1, Korifla, Waha, Miki2) obtained from ICARDA (International Center for Agricultural Research in the Dry Areas)and Zühre durum wheat variety cultivated in the region as the standart. The trials were performed as a randomized complete block design experiment with three replications in two locations. Grain yield, thousand kernel weight, hectoliter weight, protein content, semolina color and SDS value were evaluated in the study. The results of the analyses of compound variances revealed significant differences between genotypes in all the parameters except hectoliter weight. Significant differences were found between locations in terms of grain yield and thousand kernel weight and in terms of grain yield, thousand kernel weight and protein content between the genotype x location interaction. A biplot analysis method was performed to evaluate inter-trait and genotype-trait relationships. Traits related to each other and the genotypes featured in terms of particular traits were visually shown by this analysis. Promising genotypes according to the grain yield and quality characteristics based on two location averages were taken to the advanced stages of the breeding program